2015
DOI: 10.1016/j.procs.2015.05.288
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of a Magnetosphere with Implicit Particle-in-Cell Simulations

Abstract: We demonstrate the improvements to an implicit Particle-in-Cell code, iPic3D, on the example of dipolar magnetic field immersed in the flow of the plasma and show the formation of a magnetosphere. We address the problem of modelling multi-scale phenomena during the formation of a magnetosphere by implementing an adaptive sub-cycling technique to resolve the motion of particles located close to the magnetic dipole centre, where the magnetic field intensity is maximum. In addition, we implemented new open bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…As an example of these simulations, we carried out a three-dimensional simulation of a magnetosphere. The simulation setup, parameters, and main results are reported in Peng et al (2015b). In this simulation, the solar wind is subsonic as the solar wind velocity is lower than the magnetosonic Mach number.…”
Section: Dipolar Mini-magnetospherementioning
confidence: 99%
“…As an example of these simulations, we carried out a three-dimensional simulation of a magnetosphere. The simulation setup, parameters, and main results are reported in Peng et al (2015b). In this simulation, the solar wind is subsonic as the solar wind velocity is lower than the magnetosonic Mach number.…”
Section: Dipolar Mini-magnetospherementioning
confidence: 99%
“…Other approaches that do not follow the framework approach of coupling models that implement different, domain-relevant physics (Baker et al, 2009;Tóth et al, 2005) include the Vlasiator hybrid-Vlasov model (von Alfthan et al, 2014), which evolves the ion distribution function while treating the electrons as a fluid, other kinetic-fluid modeling approaches (Kolobov & Deluzet, 2019;Roytershteyn & Delzanno, 2018), and particle-in-cell models (Yang et al, 2016). Due to computational expense-or more precisely, the availability of computational resources to researchers-these kinetic simulations are currently limited to either small domains (Peng et al, 2015) or to two spatial dimensions (Innocenti et al, 2017;Jarvinen et al, 2018). The next generation of NSWP models should leverage parallelization across heterogeneous systems (Innocenti et al, 2017).…”
Section: Computational Approaches Resources and Analysismentioning
confidence: 99%
“…Outgassing is performed by injecting new plasma particles from the "surface" of the comet. A spherical shell 5dx thick is defined inside the comet and acts as buffer zone similarly to buffer zones created for enabling open boundary conditions [20]. At each time step, new computational particles are created randomly and uniformly distributed inside this spherical shell with particle density n 0e = n 0i = 1.0.…”
Section: Simulation Setupmentioning
confidence: 99%
“…The first fully kinetic model of a cometary induced magnetosphere was presented by Deca et al [18] using the iPIC3D code [19,20], the authors have shown that the dynamics of ions and electrons in the atmosphere of a weakly outgassing comet could be represented, to first order, in terms of the four-fluid system with solar wind ions, solar wind electrons, cometary ions and cometary electrons each treated by separate fluid equations. Differently from this previous work, we develop an alternative approach for modeling cometary interaction with solar wind using iPIC3D.…”
Section: Introductionmentioning
confidence: 99%